HUBUNGAN ETNIS JAWA DAN TIONGHOA DALAM NOVEL TUNGGAK-TUNGGAK JATI - Sungkowati, Yulitin (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2009)
This article tries to explore the relationship between Javanese and Chinese ethnicgroups in Tunggak-Tunggak Jati, a Javanese novel by Esmiet. The novel describes theolder Javanese generation' views of the Chinese ethnic group and vice versa based onprejudice and stereotype. But the younger Javanese and Chinese generations try toeradicate the prejudice and ethnic partition. The young Chinese generation'sconsciousness that Indonesia is their country results in the feeling that they are not differentfrom the Javanese ethnic group and they are not strangers in Indonesia. The youngJavanese generation also tries to accept the Chinese ethnic group as part of Indonesia. Thisnovel also shows that the Javanese and Chinese ethnic groups need each other in socialinteraction to establish true relationship and to respect each other through, for example,marriage.Keywords: relationship, ethnic group, Javanese, Chinese